Rewriting Australia's Racist Past: How Historians (Mis)Interpret the ‘White Australia’ Policy - Jordan, Matthew (History compass, 2005)
This article examines recent writing on the ‘White Australia’ policy and its origins in the late-nineteenth and early-twentieth centuries. For the most part, this body of work falls into two distinct and opposing categories. On the one hand, historians who take an ‘essentialist’ approach to the problem view ‘White Australia’ as a natural and inevitable by-product of Anglo-Australian racism, which, they argue, permeated Australian culture from the moment the British invaded the continent. Believing that Australian racism thus has something of an ‘inherent’ quality about it, these historians often regard any harsh or unfair decision in the immigration arena as prima facie evidence for the ‘White Australia’ policy's continuing ‘legacy’. On the other hand, ‘apologists’ for ‘White Australia’ deny that it was ever a racist policy and suggest instead that it was a sensible and at the time progressive attempt on the part of its founders to protect Australian economic standards, political conventions and cultural norms from people with vastly different attitudes and ways of life. It is the contention of this article that both interpretations succumb to an ahistorical perspective which ignores the particular ideas and circumstances that led to the policy's formal adoption in 1901. In arguing this case, it also offers a new interpretation which suggests that the rise at this time of race nationalism in Australia provides a more credible explanation for the Commonwealth's decision to embrace the principle of ‘White Australia’.